2015
DOI: 10.1016/j.biopsycho.2015.06.010
|View full text |Cite|
|
Sign up to set email alerts
|

Reduced intrasubject variability with reinforcement in boys, but not girls, with ADHD: Associations with prefrontal anatomy

Abstract: This study examined the impact of motivational contingencies (reinforcement and punishment) on Go/No-Go (GNG) task performance in girls and boys with ADHD relative to typically developing (TD) children and associations with prefrontal anatomy. Children ages 8–12 with ADHD (n=107, 36 girls) and TD controls (n=95, 34 girls) completed a standard and a motivational GNG task and associations with prefrontal cortex (PFC) surface area were examined. Intrasubject variability (ISV) was lower during the motivational com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 71 publications
(126 reference statements)
0
19
0
Order By: Relevance
“…based on DSM-IV criteria. Children taking psychotropic medications other than stimulants were excluded from participation and all children taking stimulants were asked to withhold their medication the day of and day prior to the laboratory visit, as in prior work including children on long-acting stimulants (Rosch et al, 2015; Rosch & Mostofsky, 2016; Seymour et al, 2016). Fifteen participants within the ADHD group (58%) were regularly taking a stimulant medication, 10 of which were taking long-acting formulations.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…based on DSM-IV criteria. Children taking psychotropic medications other than stimulants were excluded from participation and all children taking stimulants were asked to withhold their medication the day of and day prior to the laboratory visit, as in prior work including children on long-acting stimulants (Rosch et al, 2015; Rosch & Mostofsky, 2016; Seymour et al, 2016). Fifteen participants within the ADHD group (58%) were regularly taking a stimulant medication, 10 of which were taking long-acting formulations.…”
Section: Methodsmentioning
confidence: 99%
“…Another recent study from our laboratory expanded upon this work by including a large sample of boys and girls to address potential ADHD-related sex differences in the effect of motivational contingencies on cognitive task performance (Rosch, Dirlikov, & Mostofsky, 2015). This study showed that boys with ADHD showed similar improvements in response control with motivational contingencies as did control boys and girls, whereas girls with ADHD did not show this improvement (Rosch et al, 2015). …”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have also reported sex differences in neuropsychological functioning in children with ADHD (Hasson & Fine, 2012; O’Brien, Dowell, Mostofsky, Denckla, & Mahone, 2010; Seymour, Mostofsky, & Rosch, 2015; Wodka et al, 2008), with girls generally showing more deficits in planning and strategy mediated by prefrontal circuits, and boys showing greater impairments in more basic aspects of response control mediated by motor/ premotor circuits. Two recent studies revealed a sexually dimorphic effect of working memory demands (Seymour et al, 2015) and reinforcement (Rosch, Dirlikov, & Mostofsky, 2015) on response control. Specifically, girls with ADHD only displayed impaired response control under conditions of greater working memory demands, whereas response control was impaired among boys with ADHD regardless of working memory demands (Seymour et al, 2015).…”
Section: Introductionmentioning
confidence: 99%